The Influence of Regional Financial Independence Ratio, Pad Efficiency Ratio, and Pad Effectiveness Ratio on Regional Income of Bandung City - Nasirwan, Nasirwan; Puspita, Azzahra Yuni; Tarigan, Darryl Galed Suranta; Setiawan, Fajar (Lembaga Riset Mutiara Akbar (LARISMA), 2024)
This study aims to examine the effect of independence ratio, PAD efficiency ratio, and PAD effectiveness ratio on total revenue of Bandung. The independent variables used are the ratio of regional financial independence, the efficiency ratio of PAD, and the effectiveness ratio of PAD, while the dependent variable is the total revenue of Bandung City. Data were analyzed using multiple linear regression analysis. The results showed that the independence ratio, PAD efficiency ratio, and PAD effectiveness ratio had a significant effect on the total revenue of Bandung City both partially and simultaneously. A comprehensive understanding of the relationship between these ratios and local revenue can provide a better view in designing regional and autonomous economic development policies and effective financial management, in order to improve public welfare and sustainable economic growth.